Controllable synthesis of uniform mesoporous H-Nb2O5/rGO nanocomposites for advanced lithium ion hybrid supercapacitors. Issue 2 (13th December 2018) - Li, Shengyuan; Wang, Ting; Zhu, Wangqin; Lian, Jiabiao; Huang, Yunpeng; Yu, Yang-Yang; Qiu, Jingxia; Zhao, Yan; Yong, Yang-Chun; Li, Huaming
Abstract : Uniform mesoporous H-Nb2 O5 /rGO nanocomposites are developed for advanced lithium ion hybrid supercapacitors with remarkably high energy/power densities and excellent cycling stability. Abstract : Controllable synthesis of uniform graphene–metal oxide nanocomposites is of great interest in energy storage applications, due to the combination of their merits and the synergistic effects on the enhancement of their electrochemical performance. Herein, we report a controllable synthesis of uniform mesoporous H-Nb2 O5 /rGO nanocomposites, which exhibit higher reversible specific capacity (∼190 mA h g −1 ), and better rate capability and cycling stability (the capacitance retention is 96.5% over 500 cycles) than pristine H-Nb2 O5 microflowers, attributed to their large specific surface area (364.17 m 2 g −1 ), porous structure, and intimate interface. More remarkably, the H-Nb2 O5 /rGO-based lithium ion hybrid supercapacitor (LIHS) delivered a high energy density of 100.2 W h kg −1 at 50 W kg −1 and still retained 18.3 W h kg −1 at an ultrahigh power density of 20 000 W kg −1, as well as an excellent cycling stability. It is worth noting that some other nanocomposites, including Zn2 Ti3 O8 /rGO, Si/rGO, NaNbO3 /rGO, Nb4 N5 /rGO, and H-Nb2 O5 /2D g-C3 N4, have also been successfully synthesized by this method, demonstrating that it can be extended to prepare other functional nanocomposites for applications in energy conversion and storage, photocatalytic hydrogen production, sensors, and so on.